2021
DOI: 10.1038/s41598-021-00574-2
|View full text |Cite
|
Sign up to set email alerts
|

A multi-point heart rate monitoring using a soft wearable system based on fiber optic technology

Abstract: Early diagnosis can be crucial to limit both the mortality and economic burden of cardiovascular diseases. Recent developments have focused on the continuous monitoring of cardiac activity for a prompt diagnosis. Nowadays, wearable devices are gaining broad interest for a continuous monitoring of the heart rate (HR). One of the most promising methods to estimate HR is the seismocardiography (SCG) which allows to record the thoracic vibrations with high non-invasiveness in out-of-laboratory settings. Despite si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The FBGs are the widespread fiber optic technology employed for monitoring precordial vibrations. They are preferred to traditional electrical and mechanical sensors due to their advantageous metrological properties [ 86 ] and immunity to electromagnetic interferences, which allows their use in harsh environments such as MRI procedures in the clinical application [ 87 ]. For what concerns cardiac monitoring, the high ε sensitivity (up to 1 pm/με) and linearity in a wide range of ε values, short response time (<10 ms), and proper frequency response of FBGs make them good candidate for detecting the small and rapid heart-induced deformations of the chest surface.…”
Section: Precordial Vibrations Recording Using Fiber Bragg Grating Se...mentioning
confidence: 99%
See 3 more Smart Citations
“…The FBGs are the widespread fiber optic technology employed for monitoring precordial vibrations. They are preferred to traditional electrical and mechanical sensors due to their advantageous metrological properties [ 86 ] and immunity to electromagnetic interferences, which allows their use in harsh environments such as MRI procedures in the clinical application [ 87 ]. For what concerns cardiac monitoring, the high ε sensitivity (up to 1 pm/με) and linearity in a wide range of ε values, short response time (<10 ms), and proper frequency response of FBGs make them good candidate for detecting the small and rapid heart-induced deformations of the chest surface.…”
Section: Precordial Vibrations Recording Using Fiber Bragg Grating Se...mentioning
confidence: 99%
“…Hence, a filtering stage is required prior to the actual signal processing and HR analysis to remove the respiratory contribution and reveal the heartbeat signal. The filters used in the literature are bandpass filters with lower cutoff frequencies [ 86 ] of 0.8 Hz, 3 Hz, and 5 Hz and higher cutoff frequencies of 2 Hz, 20 Hz, and 30 Hz [ 88 , 93 , 94 , 95 ]. Often, upper and lower envelopes are additionally performed on the filtered signals to better emphasize the AO-related peak on the SCG signal [ 86 ].…”
Section: Precordial Vibrations Recording Using Fiber Bragg Grating Se...mentioning
confidence: 99%
See 2 more Smart Citations
“…The small size, low cost, nontoxicity, and electromagnetic insensitivity of biocompatible POFs make them ideal for devices applied in or near the body that shed some light on novel therapies in immunology, cardiology, neurology, oncology, and gastroenterology, among other fields [ 33 , 34 , 35 ]. For example, it is reported that wearable optical fiber based on fiber Bragg gratings can be used to monitor heart rate [ 36 ] and detect basic activities, such as walking, sitting, and squatting [ 15 ], which is promising for chronic disease prevention. Due to the increasing prevalence of diseases such as cancer, lithiasis, and angiocardiopathy, as well as the growth of minimally invasive surgery, there is an urgent need for more biocompatible, more photoconductive, and less invasive optical fibers, as well as nontoxic, tissue-like materials and low-cost, high-productivity, and versatile fabrication methods.…”
Section: Introductionmentioning
confidence: 99%